Incidence and severity of pruritus in patients delivered by caesarean section under spinal anaesthesia at Chris Hani Baragwath Hospital - Mwinyoglee, Kony Marlis (My University, 2013)
BACKGROUND AND OBJECTIVES: Local anaesthetic agent mixed with an opioid provides effective, fast and reliable onset of regional analgesia. However, the intrathecal use of opioids may have undesirable effects, one of which is pruritus (itching). The main objectives of this study were to assess the incidence and severity of fentanyl-induced pruritus in patients who received spinal anaesthesia for caesarean section at Chris Hani Baragwanath Academic Hospital, and to determine the influence of factors such as dosage of fentanyl, age, race, and socio-economic status on the perception of pruritus. METHODS: This was a prospective observational study of obstetric patients delivered by elective caesarean section under spinal anaesthesia at Chris Hani Baragwanath Academic Hospital. Regional anaesthesia was performed following a departmental protocol where patients received 0.5% bupivacaine with dextrose mixed fentanyl. The departmental protocol was used as a guideline for the mixture but the different anaesthetists were not restricted to it. Based on their practice, a range of fentanyl doses were used. The participants were observed for pruritus directly intraoperatively by the researcher, and again at approximately one hour after spinal anaesthetic administration. This last observation was complemented by means of a structured interview. Severity was assessed using a visual analogue scale. For descriptive analysis, to show a 95% confidence interval of no more than 10% around an observed percentage of patients with pruritus, a sample size of 96 participants was chosen. Page | 6 RESULTS: The overall incidence of pruritus in 96 participants who received intrathecal fentanyl was 54.2%. Pruritus occurred in 48 participants (50.0%) during the caesarean section. Four participants (4.2%), who had no pruritus intraoperatively, developed it one hour after the spinal anaesthetic was administered. The part of the body commonly affected was the nose. The severity of pruritus was more than tolerable in 6 participants (6.3%), with two of them perceiving it as unbearable. No participant reported pruritus 24 hours after the spinal anaesthetic. There was no statistically significant association between the frequency of pruritus and the dose of fentanyl, age, race and socio-economic status indicators. CONCLUSION: Pruritus is a common symptom in women undergoing caesarean section using fentanyl-containing neuraxial block. However, most cases are mild and not related to dosage. Women who complain of intraoperative or postoperative pruritus can be informed that the symptom is transient and of no serious clinical consequence.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Medicine (In the branch of Anaesthesiology). February 2013
Keywords: Pruritus; Pregnancy Outcome